2018
DOI: 10.21767/amj.2017.3270
|View full text |Cite
|
Sign up to set email alerts
|

Updated meta-analysis of the relation between heart disease and androgenic alopecia or alopecia areata

Abstract: RESEARCHPlease cite this paper as: Amamoto M, Hara K. Updated meta-analysis of the relation between heart disease and androgenic alopecia or alopecia areata. AMJ 2018;11 (1) ABSTRACT BackgroundThe relationship between baldness and heart disease is still controversial. We performed an updated meta-analysis of observational studies to evaluate the relation between heart disease and androgenic alopecia or alopecia areata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, no differences were observed in cardiovascular risk between AA patients and controls in a previous cohort study [ 8 ]. Recently, a meta-analysis conducted by Amamoto et al [ 20 ] reported that AA was not related to HDs (relative risk: 0.91; 95% CI: 0.60–1.39; p = 0 . 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no differences were observed in cardiovascular risk between AA patients and controls in a previous cohort study [ 8 ]. Recently, a meta-analysis conducted by Amamoto et al [ 20 ] reported that AA was not related to HDs (relative risk: 0.91; 95% CI: 0.60–1.39; p = 0 . 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between AGA and cardiovascular risk [ 60 ]. Amamoto Misato et al screened a total of nine studies (eight on AGA, one alopecia areata: 44,806 participants) in the Medline and Embase databases for a meta-analysis and found that compared to men without baldness, those with AGA had an increased risk of heart disease, and younger men (< 55 years or ≤ 60 years) showed a stronger correlation [ 61 ]. Salvador Arias-Santiago confirmed the association between early onset AGA and a higher cardiovascular risk in men and women groups.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%